Eyes in the Sky : Eisenhower, the CIA, and Cold War Aerial Espionage. - Brugioni, Dino (Naval Institute Press, 2011)
Dino A. Brugioni, author of the best-selling account of the Cuban Missile crisis, Eyeball to Eyeball, draws on his long CIA career as one of the world's premier experts on aerial reconnaissance to provide the inside story of President Dwight D. Eisenhower's efforts to use spy planes and satellites to gather military intelligence. He reveals Eisenhower to be a hands-on president who, contrary to popular belief, took an active role in assuring that the latest technology was used to gather aerial intelligence. This previously untold story of the secret Cold War espionage program makes full use o.